ChemInform Abstract: A Practical Guide to High‐Resolution X‐Ray Spectroscopic Measurements and Their Applications in Bioinorganic Chemistry. Issue 47 (3rd November 2016) - Kowalska, Joanna K.; Lima, Frederico A.; Pollock, Christopher J.; Rees, Julian A.; DeBeer, Serena
Abstract: Review: 91 refs.